The Investigation of Nutritional Status, Intestinal Permeability, and Quality of Life in People with Celiac Disease - Öztekin, Yeşim; Güneş, Fatma Esra; Özen Alahdab, Yeşim (Turkish Journal of Gastroenterology, 2022)
Background: Celiac disease is associated with impaired intestinal epithelial barrier integrity. Its consequences affect the nutritional status and quality of life of patients. This study aimed to determine nutritional status, intestinal permeability, and quality of life in people with celiac disease. It was researched whether patients who are non-compliant to gluten-free diet have higher serum zonulin levels and intestinal permeability. Methods: The study was completed with 44 celiac patients. Dietary records and a questionnaire were used to evaluate patients’ compliance to the gluten-free diet. Dietary records were analyzed by using a nutrition analysis program. Anthropometric measurements were taken. Body compositions were analyzed to assess the nutritional status of patients. Blood samples were collected and then zonulin levels and total serum proteins were measured to evaluate intestinal permeability. Celiac Disease Questionnaire was used to assess the quality of life scores. Results: Patients were divided into 2 groups considering compliance to the gluten-free diet and it was found that 17 patients were compliant to the gluten-free diet, and 27 patients were non-compliant to the gluten-free diet. Serum zonulin, zonulin/total protein ratio, and intestinal permeability were higher in non-compliant to the gluten-free diet group (P < .05). There was no significant difference between anthropometric measurements, Celiac Disease Questionnaire scores, daily energy, and nutrient intakes of groups (P > .05). Conclusion: The content of a gluten-free diet has a decisive role in the nutritional status and quality of life of celiac patients. Additionally, zonulin levels and intestinal permeability were higher in people with celiac disease who are non-compliant to gluten-free diet. Cite this article as: Öztekin Y, Güneş FE, Özen Alahdab Y. The investigation of nutritional status, intestinal permeability, and quality of life in people with celiac disease. Turk J Gastroenterol. 2022;33(12):1043-1049